The effects of CBD and THC in an animal model of depression – Further data from the FST. Issue 9 (September 2021) - Liu, Junhan; Scott, Brian; Burnham, McIntyre
Abstract : Objectives . Epilepsy patients frequently suffer from psychiatric comorbidities, such as depression, which seriously affect their quality of life. CBD has been reported to have not only anti‐seizure effects, but also to have possible antidepressant effects. Thus, CBD might treat not only seizures but also some of the comorbidities associated with seizures. The present study was designed to test the effects of THC, CBD and a combination of CBD and THC (15:1 ratio) in a mouse of depression (the forced swim test, FST). Previously we had reported that THC decreased immobility in the FST at one dose (2 mg/kg) and that CBD was totally ineffective. The present study was designed to re-test the effects of CBD and CBD/THC when CBD was administered at a shorter interval (30 min) before testing. Methods . Adult, male CD1 mice were injected i.p. with CBD (0, 15, 30, 60, 120, 240 mg/kg), THC (0, 0.5, 1, 2, 4, 8 mg/kg), CBD + THC (0, 15 + 1, 30 + 2, 60 + 4, 120 + 8 mg/kg) or imipramine (positive control, 0, 30 mg/kg). Subjects were either tested in the FST (6mins) or in open field arena (10mins). CBD and THC were both injected 30mins prior to testing. N = 6–12 for each dose. Results . As previously reported, imipramine (positive control) decreased immobility times at 30 mg/kg. THC also decreased immobility time in the FST at only one dose, 2 mg/kg (lower and higher doses were ineffective). CBD – injected 30 min pretest – had nearly significant effects on immobility at 60 mg/kg. CBD + THC significantly decreased immobility at 30/2mg/kg and 120/8 mg/kg, with near significant effects at 60 mg/kg. None of the drugs affected open field activity at any dose. Conclusions . CBD tested at the shorter interval of 30 minutes showed nearly significant effects in the FST. In combination with 2 mg/kg THC, significant CBD effects were seen at 30 and 120 mg/kg of CBD, with nearly significant effects seen at 60 mg/kg. Conceivably, a combination of CBD and THC might be useful in patients with combined seizures and depression. The cannabinoids used in this work were donated by MedReleaf/Aurora who also supplied partial funding for the work. Partial funding was also supplied by EpLink – The Epilepsy Research Program of the Ontario Brain Institute.